Determinants for substrate specificity of the bacterial PP2C protein phosphatase tPphA from Thermosynechococcus elongatus. (23rd January 2012) - Su, Jiyong; Forchhammer, Karl
<x xml:space="preserve">Abstract</x> Members of the Mg2+‐ or Mn2+‐dependent protein phosphatases/PP2C‐like serine/threonine phosphatases (PPM/PP2C) are abundant and widely distributed in prokaryotes and eukaryotes, where they regulate diverse signal transduction pathways. Despite low sequence conservation, the structure of their catalytic core is highly conserved except for a flexible loop termed the flap subdomain. Bacterial PPM/PP2C members without C‐ or N‐terminal regulatory domains still recognize their substrates. Based on the crystal structure of tPphA (a PPM/PP2C member from the cyanobacterium Thermosynechococcus elongatus), variants of tPphA were generated by site‐directed mutagenesis to identify substrate specificity determinants. Furthermore, a PPM/PP2C chimera containing the tPphA catalytic core and the flap subdomain of human PP2Cα was also generated. tPphA variants and the chimera were tested towards different artificial substrates and native phosphorylated PII. A binding assay combining chemical crosslinking and pull‐down was designed to analyze the binding of the various phosphatase variants to phosphoprotein PII. Together, these data showed that the metal 1–metal 2 cluster in the catalytic center, but not the catalytically active metal 3, is required for the binding of phosphorylated substrate. Residues outside the catalytic center are pivotal for the recognition and turnover of phosphorylated protein substrate. In particular, a histidine residue (His39) of tPphA was identified to play a specific role in protein substrate dephosphorylation. Furthermore, mutations in the variable flap subdomain can affect enzyme activity as well as substrate specificity. Structured digital abstract tPphA binds to P‐II by cross‐linking study (View Interaction: 1, 2, 3, 4, 5, 6, 7, 8)